Cerebral hemorrhage as the initial symptom of delayed diagnosis of childhood pheochromocytoma - Alla Salloum; Victor Khoury; Ferhad Hemi; Akil Khaddam; Ammar Omran (Elsevier, 2022)
Pheochromocytoma is a rare catecholamine secreting tumor originating from the chromafine cells of the adrenal medulla, so it is an unusual cause of surgical hypertension and is extremely rare in pediatric population. we present a case of 12-year-old girl who had an intracranial hemorrhage as the first demonstration due to blood hypertension of undiagnosed pheochromocytoma.